Aflatoxins in bird feed collected from various areas of Lahore city (Bangladesh Journal of Scientific and Industrial Research, 2021)
The objective of this study was to estimate total aflatoxin in bird feed. Total 50 birds feed samples were collected from different markets and birds shops in Lahore. Total aflatoxin B1, B2, G1, and G2 were estimated using the Thin Layer Chromatography (TLC) method. The daily intake of aflatoxin in bird's feed is a 300ppb threshold by FDA. Total 50 samples were examined, among them 22% were contaminated with aflatoxin B1 and B2 and the rest of 40% samples were contaminated only with aflatoxin B1. Aflatoxin G1 and G2 were not detected in any feed. The results showed that 42% of samples were contaminated within the permissible limit, 20% were unfit due to having above the allowable limit, and 38% were fit, which did not show any aflatoxin. The current study has demonstrated the easy way of providing the determination of aflatoxin in bird’s feed.Bangladesh J. Sci. Ind. Res.56(4), 249-254, 2021